Paclitaxel Inhibits Synoviocyte Migration and Inflammatory Mediator Production in Rheumatoid Arthritis - Chen, Xiaochen; Lin, Haofeng; Chen, Jinyang; Wu, Lisheng; Zhu, Junqing; Ye, Yongnong; Chen, Shixian; Du, Hongyan; Li, Juan (Frontiers in Pharmacology, 2021)
Activated fibroblast-like synoviocytes (FLSs) play a crucial role in the pathogenesis and progression of rheumatoid arthritis (RA). There is an urgent need to develop new drugs that can effectively inhibit the abnormal activation of RA-FLS. In the present study, the RA-FLS cell line, MH7A, and mice with collagen-induced arthritis (CIA) were used to evaluate the therapeutic effects of paclitaxel (PTX). Based on the results, PTX inhibited the migration of RA-FLS in a dose-dependent manner and significantly reduced the spontaneous expression of IL-6, IL-8, and RANKL mRNA and the TNF-α-induced transcription of the IL-1β, IL-8, MMP-8, and MMP-9 genes. However, PTX had no significant effect on apoptosis in RA-FLS. Mechanistic studies revealed that PTX significantly inhibited the TNF-α-induced phosphorylation of ERK1/2 and JNK in the mitogen-activated protein kinase (MAPK) pathway and the activation of AKT, p706SK, 4EBP1, and HIF-1α in the AKT/mTOR pathway. Moreover, PTX alleviated synovitis and bone erosion in CIA mice. In conclusion, PTX inhibits the migration and inflammatory mediator production of RA-FLS by targeting the MAPK and AKT/mTOR signaling pathways, which provides an experimental basis for the potential application of PTX in the treatment of RA.